ANALISIS PENGARUH KUALITAS PELAYANAN, HARGA DAN KUALITAS JARINGAN INTERNET TERHADAP KEPUASAN PELANGGAN PRODUK INDIHOME DI PT TELKOM INDONESIA, TBK WILAYAH RT 008 RW 002 PETUKANGAN SELATAN JAKARTA SELATAN - Albiansyah, Albiansyah; Bayu Adji, Seto; Azhar, Arizal (Management Research and Business Journal, 2024)
This research aims to determine the influence of Service Quality, Price and Internet Network Quality on Customer Satisfaction of Indihome Products at PT Telkom Indonesia, Tbk Region Rt 008 Rw 002 Petukangan Selatan South Jakarta, and a sample size of 56 respondents in the Petukangan Selatan area, South Jakarta using techniques data collection through distributing questionnaires. The data analysis method used in this research is quantitative data analysis using multiple linear regression analysis tests, coefficient of determination tests (R2), partial tests (t) and simultaneous tests (F). The results of this research show that multiple linear regression analysis has the equation Y = 4.650 + 0.422X1 + 0.134X2 + 0.323X3. The coefficient of determination test results (R2) have an Adjusted R Square value of 0.836 or 83.6%, meaning that the Customer Satisfaction variable is explained by the variables Service Quality, Price and Internet Network Quality, while 16.4% is explained by other variables outside the research. The results of the t test show that Service Quality (X1) on Customer Satisfaction (Y) has a t count of 5.302 > t table 2.0065 and a significance level of 0.000 < 0.05, so there is a partially significant influence between the service quality variables on customer satisfaction. Price (X2) on Customer Satisfaction (Y) has t count 2.318 > t table 2.0065 and a significance level of 0.024 < 0.05, there is a partially significant influence between the price variable on customer satisfaction. and the Internet Network Quality variable (X3) on Customer Satisfaction (Y) has t count 3.955 > t table 2.0065 and a significance level of 0.000 > 0.05, there is a partially significant influence between the internet network quality variable on customer satisfaction. The results of the F test show that F count is 94.136 > F table 2.78 with a significance level value of 0.000 < 0.05, so service quality, price and internet network quality together have a significant effect on customer satisfaction.